Differences between Breast Cancer Reconstruction and Institutionally Established Normative Data Using the BREAST-Q Reconstruction Module: A Comparative Study. Issue 6 (June 2020) - Klifto, Kevin M.; Aravind, Pathik; Major, Melissa; Payne, Rachael M.; Shen, Wen; Rosson, Gedge D.; Cooney, Carisa M.; Manahan, Michele A.
Abstract : Background: Evidence is limited for BREAST-Q scores in women without breast cancer or breast surgery to establish baseline values for clinical interpretation. The primary aim of this study was to compare differences in breast satisfaction and quality of life in women without breast cancer and without breast surgery to patients undergoing breast reconstruction using the BREAST-Q. Methods: The authors performed a single-center, patient-reported outcomes comparative study. A sample of 300 women attending gynecology appointments completed a study-specific demographics form and preoperative BREAST-Q reconstruction module. Eligible women had no history of breast cancer or breast surgery and were not currently pregnant (control group). The authors compared prospectively collected control group data to demographics and preoperative and 12-month postoperative BREAST-Q scores in 300 breast reconstruction patients, retrospectively selected from a prospectively collected registry. Results: Control group BREAST-Q scores were higher in Satisfaction with Breasts (mean, 59.3 versus 55.3; p < 0.042) and Physical Well-being Chest scores (mean, 84.1 versus 78.8; p < 0.001), and lower for Physical Well-being Abdomen scores (mean, 81.9 versus 88.7; p < 0.001) when compared to breast reconstruction patients' preoperative scores. When compared with breast reconstruction patients' 12-month postoperative scores, control group scores were lower in Satisfaction with Breasts (mean, 59.3 versus 65.5; p < 0.002) and Psychosocial Well-being (mean, 69.5 versus 76.2; p < 0.001) and higher in Physical Well-being Chest (mean, 84.1 versus 78.2; p < 0.001). Conclusions: The authors found differences in preoperative and 12-month postoperative BREAST-Q scores between breast reconstruction patients and a comparable control population. Establishing normative BREAST-Q data could serve as an important baseline for breast outcomes research and better understanding of patients' ability to recover quality of life following reconstruction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.